Considerations for continued expansion of the Brazilian post-graduate system - McManus, Concepta; Baeta Neves, Abilio Afonso; Carvalho, Carlos Henrique; Souza Filho, Antonio Gomes; Freire, Denise Maria Guimarães; Fioravanti, Maria Clorinda Soares; Báo, Sônia Nair; de Medeiros, Isac Almeida; Diniz Filho, José Alexandre; Diaz, Bruno Lourenço; de Carvalho, Ernani Rodrigues; Audy, Jorge Luís Nicolas; et al. (Frontiers in Education, 2023)
The number of programs and students in the Brazilian postgraduate system has doubled in the last 10 years. This has implications for the quality and financing of these programs as well as for the development of the regions where they are set. This study aims to investigate the reasons and limitations for the continued expansion of the Brazilian postgraduate system. Data (2011 to 2020) for this study came from: (i) the “Sucupira” postgraduate database from the Coordenação de Aperfeiçoamento de Pessoal de Nível Superior (CAPES), (ii) Instituto Nacional de Estudos e Pesquisas Educacionais Anísio Teixeira (INEP), (iii) Brazilian Institute of Geography and Statistics (IBGE), (iv) InCites® and Web of Science data, and (v) questionnaire and meetings with the deans for Higher Education Institutions (HEIs) in Brazil. Data analyses included regression over time, frequency chi-square, and correspondence analyses. Different types of institutions in different regions showed varying opinions, with higher expectations for expansion in smaller, newer institutions, especially private ones. While the HEIs in the Northern region believe that the master’s degree is to correct undergraduate flaws, the HEIs in the South and Central regions and the community believe that the master’s degree should develop professional skills. In contrast, the larger HEIs with older postgraduate programs in all regions believe in direct doctorate strategy. The reasons for creating new post-graduate programs involved following the institution’s general guidelines for private and community HEIs and granting the lecturers’ wishes or constant expansion depending on region, North, Northeast, and Central regions, as well as for creating medium-sized state universities. State-of-the-art research or the interests of society were prevalent for the largest and oldest HEIs. Continued expansion of the Brazilian postgraduate system needs to take into account factors including the demand for the program, regionalization, the quality of the programs, the means of funding, and the student vacancies existing in programs with high grades, among other challenges.